Synopsis of Himatanthus (Apocynaceae, Rauvolfiodieae: Plumerieae) species from Peru - Guerra, CAA (2016)
This study is part of a doctoral dissertation of the first author, developed at the Escuela Doctoral Franco Peruana en Ciencias de la Vida, Universidad Peruana Cayetano Heredia and École Doctorale GAIA Biodiversité, Agriculture, Alimentation, Environnement, Terre, Eau, Université de Montpellier, France. We thank the directors and curators of the herbaria listed in the Material & Methods for loan of material, providing digital images, and for providing working space during our visits. This project was supported by a Franco-Peruvian doctoral fellowship from the National Council for Science, Technology and Technological Innovation (Consejo Nacional de Ciencia, Tecnología e Innovación Tecnológica, CONCYTEC) of the Peruvian Government, and the French Embassy in Peru. The Institut de Recherche pour le Developpement (IRD) also supported this project by sponsoring field work in Peru through the Laboratorio Mixto Internacional Andino Amazónico en Química de la Vida led by Michel Sauvain, travel expenses to the Herbier de Guyane (CAY), Cayenne and field work in French Guiana by the first author. The Research Institute of the Peruvian Amazon (Instituto de Investigaciones de la Amazonía Peruana, IIAP) allowed us to carry out part of the fieldwork at its biological station within the Allpahuayo Mishana National Reserve. Permission to study and collect in the Peruvian Amazon were granted by the Servicio Nacional Forestal y de Fauna Silvestre (SERFOR) and the Servicio Nacional de Areas Naturales Protegidas (SERNANP) of Peru. Nicole Mitidieri, Ricardo Zárate and Tony Mori collected and donated part of the specimens included in this study. Marcos Ríos also contributed fertile specimens as part of Project IRB 27 (Inventario Rápido Biológico) Tapiche-Blanco of the Río Tapiche, a remote area of the Peruvian Amazon. We would like to thank Joseph Kirkbride (Smithsonian Institution, Washington, USA), John Wiersema (U.S. National Arboretum, USDA-ARS, Beltsville, USA), Mary Endress (Zurich University, Switzerland), Michael Nee (Missouri Botanical Garden, St. Louis, USA), and the nonymous reviewers for valuable comments and corrections to the manuscript.